Effect of glass and polyacid preparations on the strength of glass ionomer cements for dental applications - Naruporn Monmaturapoj; Siriporn Tanodekaew; Wiwaporn Soodsawang (Songklanakarin Journal of Science and Technology (SJST), 2009)
Glass ionomer cements (GICs), widely used as restorative materials in dentistry, are principally composed of fluoroaluminosilicateglass powder combined with a water-soluble polyacid. The investigation of new glass compositions and polyacid components are very important to improve the mechanical properties of these cements. The objective of this work was to prepare glass ionomers and polyacids for the use as GICs. The effects of spherical bodies, Al2O3:SiO2 ratios, replacing CaO by SrO, and ZrO2 adding in glass powder in combination with the variation of acidic copolymer concentration on the compressive strength were investigated and discussed.